Bahaya Label Negatif Terhadap Pembentukan Konsep Diri Anak Dengan Gangguan Belajar - Kushendar Kushendar; Aprezo Pardodi Maba (Nidhomul Haq : Jurnal Manajemen Pendidikan Islam, 2017)
Negative labelling defined as giving name to a person or group based on the deficiencies or advantages they have. Labeling often poses negative things into a person when it did not give appropriately. Self-concept related to self-like views, self-evaluation results and self-expectations and these become the shaping factor of self-concept. When child with learning disability labeled as "the slacker" or "the stupid" it is giving negative impact to his or her self-concept. Understanding the harmful of negative labelling could be a preventive strategy to avoiding negative labelling toward child with learning disability.